Kærligheden, mesteren og mesterlæren - Nyborg †, Ole (Grundtvig-Studier, 2015)
Kærligheden, mesteren og mesterlæren Ole Nyborg The Concept of Love, the Master, and the Aprentice[1] In his dissertation Nyborg argues that Grundtvig’s sermons promote an educational theory that differs from the one found through standard interpretations of Grundtvig’s pedagogical thinking. In chapter three, which is printed in the journal, Nyborg describes a cognitive schema of fatherliness and paternalism that strongly influences how Grundtvig presents the concept of love in his sermons between the years of 1832 and 1849. Nyborg argues specifically that Grundtvig frequently interprets the expression “God is love” into an idea of paternal direction, chastisement, and education. Grundtvig contends that Christians must love their neighbors in the same way, within a hierarchical or asymmetrical relation. Christians emulate the Father by acting as stronger, more knowing, fatherly agents towards their neighbors. The purpose of this love becomes evident in the didactic element in Grundtvig’s sermons. Christians channel their love into thinking, feeling, relating, and acting to save their neighbors from the evil, darkness, ungodliness, carnality, and immorality of the world. Christian disciples learn this behavior through a sort of apprenticeship, which like any training is meant to help the apprentice grow and become like the master. Christian disciples get their training in the so-called school of the Lord, where the Master as strong father teaches them suffering, discipline, renunciation, and aspiration. Disciples are constantly tempted to leave he school and return to the pleasures of the world. In his sermons Grundtvig connects this type of school with its pedagogical theory with descriptions in the New Testament of the learning community of Christ and his disciples. The teleological end-point of this demanding and difficult education is a fundamental transformation of the motivation and character of the disciples. They begin their education contaminated and damaged physically, mentally, and morally; they end it justified, sanctified, and purified. Their motivation, thoughts, feelings, values, aspiration, nature, and personality are transformed. They move closer and closer to the central identity, competence, and nature of their Master who is the magnificent paragon and the pattern of love, morality, spirituality, and virtue. [1] Ole Nyborg died on 18 February 2014 – see the obituary in this journal. On 29 November 2013, he had defended his PhD thesis, titled Grundtvig og kærligheden – Kærlighedsforståelsen i N.F.S. Grundtvigs prædikener (Grundtvig and Love: Love Comprehension in N.F.S. Grundtvig’s sermons), at the Faculty of Theology in Copenhagen. In consultation with the family of Ole Nyborg and Niels Henrik Gregersen it was decided to publish the third chapter of the dissertation, which concerns the vision of religious educational upbringing in Grundtvig’s sermons. This summary is inspired by the summary in Nyborg’s thesis pp. 253-253. The thesis can be downloaded at: http://curis.ku.dk/ws/files/92172145/Ole_Nyborg_Grundtvig_og_Kaerligheden_til_CURIS.pdf ( 1. November 2014). The editors.